Importancia del uso de microorganismos benéficos para el control de enfermedades en cultivo de ciclo cortó en el Ecuador - Coque Santana, Diana Estefany (2025)
In this research, the importance of beneficial microorganisms in agriculture is increasingly relevant due to their ability to control diseases as a sustainable alternative in short-cycle crops. The general objective is to establish the importance of the use of beneficial microorganisms in the control of diseases in short-cycle crops in Ecuador. The methodology of the research is determined to be based on collecting information from recent scientific articles, web pages and virtual libraries that allow the development of this study. The results highlight the positive impact of bacteria such as Rhizobium ssp., Azotobacter spp., Azospirillum spp. and Lactobacillus spp. that improve nitrogen fixation and increase soil biomass, likewise, fungi such as Trichoderma spp., Beauveria bassiana and Metarhizium anisopliae help control pathogens and pests. The implementation of these microorganisms reduces the dependence on synthetic fertilizers and pesticides, which optimizes nutrient absorption, increases yields by up to 20% and reduces soil contamination. In conclusion, the use of beneficial microorganisms not only controls diseases in short-cycle crops, but also promotes more sustainable, efficient and profitable agriculture, preserving soil biodiversity and caring for the health of small and medium-sized farmers.